Prospective Medicinal Plants and Their Phytochemicals Shielding Autoimmune and Cancer Patients Against the SARS-CoV-2 Pandemic: A Special Focus on Matcha - Kiriacos, Caroline Joseph; Khedr, Monika Rafik; Tadros, Miray; Youness, Rana A. (Frontiers in Oncology, 2022)
Background: Being “positive” has been one of the most frustrating words anyone could here since the end of 2019. This word had triumphed over the globe due to the high infectious potential of SARS-CoV-2. SARS-CoV-2 exposed all citizens to the light of risk; yet, a red alarming sign has been directed to cancer and immune-compromised patients in particular. These groups of patients are not only more prone to catch the virus but they are also more liable to its deadly consequences; something that urged the research community to seek other effective and safe solutions that could be used as a protective measurement for cancer and autoimmune patients during the pandemic era. Aim: The authors aimed to spot the light on specific herbal remedies that showed potential anti-cancer activity, immuno-modulatory role, and promising anti-SARS-CoV-2 actions. Methodology: To reach the purpose of the review, research was conducted at the States National Library of Medicine (PubMed). For the search in databases, the descriptors used were: "COVID-19"/ "SARS-CoV-2", "Herbal Drugs", "Autoimmune diseases", "Rheumatoid Arthritis", "Asthma", "Multiple Sclerosis", "Systemic Lupus Erythematosus" "Nutraceuticals", "Matcha", "EGCG", "Quercetin", "Cancer" and key molecular pathways. Results: This manuscript reviewed most of the herbal drugs that showed a triple-action concerning anti-cancer, immunomodulation, and anti-SARS-CoV-2 activities. A special focus was directed on the “Matcha” as a novel potential protective and therapeutic agent to cancer and immunocompromised patients during the SARS-CoV-2 pandemic. Conclusion: This review sheds the light on the pivotal role of "Matcha" as a trio-acting herbal tea having a potent anti-tumorigenic effect, immunomodulatory role and proven anti-SARS-CoV-2 activity; thus provides a powerful shield for high risk patients such as cancer and autoimmune patients during the pandemic era.